2022
DOI: 10.3389/fpsyg.2021.794112
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Addiction and Eysenck's Personality Traits Among Chinese Adolescents: A Meta-Analysis

Abstract: With the quickly rising popularity of smartphone among adolescents over the past decade, studies have begun to investigate the relationship between smartphone addiction and Eysenck's personality traits. Despite numerous studies on this topic, however, findings have been mixed and there is a lack of consensus regarding this relationship. Thus, this meta-analysis aimed to explore the relationship between smartphone addiction and Eysenck's personality traits in Chinese adolescents, as well as its possible moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…On the other hand, loneliness, anxiety (including social anxiety), and depression constituting internalizing symptoms are considered not only consequences, but also important factors in the development and severity of behavioral addictions [ 30 , 31 , 32 ]. Thus, people with a high level of neuroticism characterized by an increased tendency to experience negative emotions and feelings—sadness, regret, envy, jealousy, anxiety—are more susceptible to behavioral addictions [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, loneliness, anxiety (including social anxiety), and depression constituting internalizing symptoms are considered not only consequences, but also important factors in the development and severity of behavioral addictions [ 30 , 31 , 32 ]. Thus, people with a high level of neuroticism characterized by an increased tendency to experience negative emotions and feelings—sadness, regret, envy, jealousy, anxiety—are more susceptible to behavioral addictions [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with a high tendency to experience neuroticism are typically described as having a neurotic personality ( McCrae and Sutin, 2018 ). Individuals with highly neurotic personality traits often experience negative psychological conditions such as anxiety, stress, and depression, and display large mood fluctuations, strong responses to stimuli, and sometimes even irrational behaviors ( Brandes and Tackett, 2019 ; Friedman, 2019 ; Xiong et al, 2022 ).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Students accounted for 29.6%, ranking first in terms of occupation among all Chinese Internet users. As a group of college students with rapid ideological development and easy to accept new things, mobile phones have a subtle impact on their growth and development ( Mei et al, 2018 ; He et al, 2019 ; Xiong et al, 2022 ). For college students, mobile phone use is a double-edged sword.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the metacognition explored in this study is the metacognition of smartphone use, what is the relationship between personality and smartphones use? Some studies have found that personality traits could also be important factors contributing to problematic smartphone use or smartphone addiction ( Demkow-Jania et al, 2021 ; Xiong et al, 2021 ). High neuroticism and low conscientiousness predicted problematic smartphone use well ( Horwood and Anglim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%